Community and Federal Collaboration to Assess Pregnancy Outcomes in Alaska Native Women, 1997-2005. - Kim, Shin; England, Lucinda; Shapiro-Mendoza, Carrie; Wilson, Hoyt; Klejka, Joseph; Tucker, Myra; Lewis, Claire; Kendrick, Juliette (Maternal & Child Health Journal, 2014)
The objectives are to report the estimated prevalence of pregnancy complications and adverse pregnancy outcomes in a defined population of Alaska Native women and also examine factors contributing to an intensive and successful collaboration between a tribal health center and the Centers for Disease Control and Prevention. Investigators abstracted medical record data from a random sample of singleton deliveries to residents of the study region occurring between 1997 and 2005. We used descriptive statistics to estimate the prevalence and 95 % confidence intervals of selected pregnancy complications and adverse pregnancy outcomes. Records were examined for 505 pregnancies ending in a singleton delivery to 469 women. Pregnancy complication rates were 5.9 % (95 % CI 4.0, 8.4) for gestational diabetes mellitus, 6.1 % (95 % CI 4.2, 8.6 %) for maternal chronic hypertension and 11.5 % (95 % CI 8.8, 14.6) for pregnancy associated hypertension, and 22.9 % (95 % CI 19.2-26.5 %) for anemia. The cesarean section rate was 5.5 % (95 % CI 3.5, 7.5) and 3.8 % (95 % CI 2.3, 5.8) of newborns weighed >4,500 g. Few previous studies reported pregnancy outcomes among Alaska Native women in a specific geographic region of Alaska and regarding the health needs in this population. We highlight components of our collaboration that contributed to the success of the study. Studies focusing on special populations such as Alaska Native women are feasible and can provide important information on health indicators at the local level.